“Mine anger hath beene just”: Feeling Familicide in the Early Modern Ottoman Court in Thomas Goffe’s The Raging Turk and The Courageous Turk - Hussain, Aisha (Renaissance and Reformation / Renaissance et Réforme, 2025)
This article offers an analysis of Thomas Goffe’s portrayal of Turkish persons in his plays The Raging Turk (1618) and The Courageous Turk (1619), which represent specific English understandings of Ottoman beliefs about proper sensorial behaviour in political and religious contexts, in particular those concerning law and justice. The article offers a counter to the “Othering” narrative by arguing that specific characters are represented in sensorially positive manners to protect English political interests, especially related to murders within the family that are portrayed in the national interests of Ottoman leaders. The article seeks to facilitate this aim by examining Goffe’s portrayals of Ottoman rulers and the role that sensory elements played in his representations of their power and legitimacy. In particular, the article focuses on death rituals of official violence—executions—and how the senses were involved in their depiction. It grows out of historiographical debates on perceptions of the Other and stereotypes of Ottoman Islam and Orientalism. In doing so, the article seeks to demonstrate that Goffe’s work provides an alternative view of “the Turk” from that of many contemporaries—one that is less about brutality and barbarism and more about the constraints of law in a regulated polity. It arrives at the consensus that Goffe’s representation of male Turkish rulers is demonstrative of an emerging Turkish stereotype that is less about violence for its own sake and more about lawful, justified violence within the bounds of Ottoman culture and legal institutions.